Gut–Brain–Microbiota Axis in Irritable Bowel Syndrome: A Narrative Review of Pathophysiology and Current Approaches - Mihaela Stoyanova; Vera Gledacheva; Stoyanka Nikolova (Applied Sciences)
Irritable bowel syndrome (IBS) is a widespread functional gastrointestinal disorder characterised by chronic abdominal discomfort and altered bowel habits. Despite its high impact on life quality and healthcare systems, the initial pathophysiology of IBS is not yet fully understood. The present narrative review aims to synthesise and integrate recent evidence regarding the multifactorial nature of IBS, focusing on the interplay between gut–brain interactions, microbiota, and immune responses, without proposing a novel model but rather reinforcing and updating existing conceptual frameworks. A comprehensive literature search of relevant studies published in English during the past two decades was conducted using Pub-Med, Scopus, and Google Scholar. The selected articles were thoroughly evaluated to provide a complete overview of IBS-related research. The review demonstrates that IBS is not only a multifactorial condition involving gut–brain axis dysregulation, altered gut motility, visceral hypersensitivity, and microbiome disturbances, but also a crucial psychosocial factor. Modern therapeutics targeting the microbiota and neurogastroenterology pathways show promising results but require further investigation. IBS represents a heterogeneous disorder with complex interrelated mechanisms. Improvements in understanding its multifaceted nature are of paramount importance in developing more effective diagnostic and therapeutic approaches. Continued research is essential to unravel the intricacies of IBS and improve patient outcomes.